PEMBUATAN BIODESEL DARI BERMACAM MINYAK GORENG BEKAS DENGAN PROSES TRANSESTERIFIKASI - Alik Kandhita Febriani; Arie Nurmala Dewi (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Today, Biodiesel attracts the Scientists to do further research, because Biodiesel can be used as a substitute for fossil fuel. Biodiesel can be made from various type of plant oils. In this research the authors choses palm oil that has been used for the purpose of utilizing the waste. Waste palm oil is classified into two types: one-time used of cooking oil and several times used. Stages of the manufacture of Biodiesel from waste palm oil is FFA (Free Fatty Acid) decreasing by esterification and the second process is the transesterification. After passing through two stages of the process, followed by calculating the weight percent of FAME (Fatty Acid Methyl Ester) by GC (Gas Chromatography) analysis. The result is 80,58% for one time use palm oil with component that are suspected as methyl ester is 47,40%, while several times-used palm oil has 89,67% weigh percent of FAME with component that are suspected as methyl ester is 53,46%, so the several times-used palm oil produces methyl ester yield more than one time-used palm oil. From the result of the preliminary analysis, it continues to the next analysis, those are physical analysis (density, viscosity) and chemical analysis (acid number, saponification number). This analysis is done in 16 times runs with the variables, methanol : palm oil weight ratios are 0,75:1; 1,56:1; 2,34:1 dan 3,13:1, and time of transesterification are 60, 70, 80, and 90 minutes. From the analysis results, the best result is 12th run with 1 : 2,34 methanol : oil ratio and 90 minutes transesterification. It has 0,87 gr/ml of density, 2,24 cst of viscosity, 0,26 mg KOH/gr of acid number, and 336 mg KOH/gr of saponification number.